Legal Protection for the Citizenship Status of Children from Mixed Marriages in the Mandalika Special Economic Zone - Ayang Afira Anugerahayu; Febrihadi Suparidho (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The development of the Mandalika Special Economic Zone as a global tourist destination has strengthened social interactions between Indonesians and foreigners, including through intermarriages. This phenomenon has given rise to various family law issues, particularly regarding the citizenship status of children from these marriages. The issues encompass not only child citizenship norms but also the implementation of population administration, immigration documents, and the actual guarantee of children's civil rights. This study aims to analyze the legal provisions for citizenship of children from intermarriages under Indonesian law and evaluate the effectiveness of legal protection for these children in the Mandalika Special Economic Zone (SEZ). The method used is a normative-empirical approach with a socio-legal approach. The normative analysis examines Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia, Law Number 1 of 1974 concerning Marriage as amended by Law Number 16 of 2019, along with regulations on population administration and child protection. Meanwhile, the empirical approach explores social and administrative practices in the Mandalika Special Economic Zone. The findings indicate that, normatively, limited dual citizenship has protected children from intermarriages. However, field practice remains hampered by delays in marriage registration, inconsistencies in documents between countries, lack of coordination between agencies, and limited public legal knowledge regarding the status of children. Recommendations include strengthening integrated administrative services based in international tourism areas, harmonizing population and immigration regulations, and providing legal education for mixed-marriage couples to ensure legal certainty and children's rights.